Hubungan Produktivitas Pertanian Tembakau dengan Fluktuasi Ekonomi Studi Kasus pada Masyarakat Desa Ampel, Kecamatan Wuluhan kabupaten Jember - Hamdi, Muhammad; musthofa H, Dovi iwan; saddad, Anwar (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2023)
The majority of the population in East Java works as farmers because they are supported by a suitable climate and extensive land. For generations, they have relied on agriculture as their primary source of income, alongside trade and production. Therefore, it is hypothesized that the productivity of tobacco farming will influence the farmers' economy. However, an analysis of the relationship between tobacco farming productivity and economic fluctuations in the community is necessary. This research aims to determine the extent of the relationship between tobacco farming productivity and the community's economy in the study area. Consequently, this study will serve as a reference for improving the community's economy through the tobacco farming sector. The research employs a quantitative research method with correlation analysis. The population consists of 798 individuals, and a sample of 70 was obtained using questionnaires and interviews. The research findings indicate that tobacco farming productivity significantly affects the fluctuations in the community's economy. Thus, it can be concluded that the village of Ampel has a strong dependence on the agricultural sector, especially tobacco, and efforts are needed to continually increase farming productivity.